Effects of Financial Literacy On Financial Decision-Making and Household Wealth Creation - Hurson, Isaac Bright; Frimpong, Siaw; Dorhetso, Samuel; Yanney, Emmanuel; Noi, Ruby Norkor (International Journal of Business, Management and Economics, 2025)
This study investigates the relationship between financial literacy and household wealth creation among employees in Ghana, focusing on how demographic factors such as age, education level, and gender moderate this relationship. Using primary data collected through a cross-sectional survey and analyzed through partial least squares structural equation modeling (PLS-SEM), the study tests two hypotheses related to financial literacy and its impact on household wealth. The findings indicate that financial literacy has a significant positive effect on household wealth creation, suggesting that an increase in financial literacy corresponds to an increase in household wealth. The study also finds that demographic factors, particularly age and education level, significantly moderate the relationship between financial literacy and household wealth. Gender, however, does not show a significant moderating effect. These results align with previous studies in developed economies, but offer new insights into the relevance of financial literacy in the context of a developing economy like Ghana. The study is underpinned by social exchange theory and contributes to the growing body of literature on financial literacy and wealth creation, with policy and practical implications for improving financial education and wealth management practices among employees in Ghana.